Generative design : visualize, program, and create with JavaScript in p5.js - Bohnacker, Hartmut, 1972-; Gross, Benedikt, 1980-; Laub, Julia, 1980-; Lazzeroni, Claudius (Princeton Architectural Press, 2018)
Generative design, once known only to insiders as a revolutionary method of creating artwork, models, and animations with programmed algorithms, has in recent years become a popular tool for designers. By using simple languages such as JavaScript in p5.js, artists and makers can create everything from interactive typography and textiles to 3D-printed furniture to complex and elegant infographics. This updated volume gives a jump-start on coding strategies, with step-by-step tutorials for creating visual experiments that explore the possibilities of color, form, typography, and images. Generative Design includes a gallery of all-new artwork from a range of international designers-fine art projects as well as commercial ones for Nike, Monotype, Dolby Laboratories, the musician Bjork, and others.- Resumé vydavatel